Bacteriological Analysis of Groundwater of Karachi - Haq, Tooba; Urooj, Mah-; Perveen, Fahmida; Sultana, Liaquat (Biological Sciences - PJSIR, 2007)
The leve l of microbial contami nation i n open we l l s i n sel ected areas of the Karach i ci ty was stud i ed i n consideration of the heal th of th e i n h abi tants of the areas. A total of 1 1 5 we l l water sampl es were col l ected and exam i n ed for total bacteri a l count and counts of col ifonn, faecal col iform and Pseudomonas aeruginosa. The micro biological anal ys i s y ielded presence of col i form and faecal col iform i n 66.63% and 60. 89% of the samples exam i ned, respecti vel y, w h i le, Pseudo111011as aeruginosa was detected i n 30% of the ground water sam pl es. 84.34% of the water sampl es were found u n sat i sfactory as per W HO standard s.